Immunotoxicity of mercury: Pathological and toxicological effects. (2nd January 2017) - Maqbool, Faheem; Niaz, Kamal; Hassan, Fatima Ismail; Khan, Fazlullah; Abdollahi, Mohammad
ABSTRACT: Mercury (Hg) is toxic and hazardous metal that causes natural disasters in the earth's crust. Exposure to Hg occurs via various routes; like oral (fish), inhalation, dental amalgams, and skin from cosmetics. In this review, we have discussed the sources of Hg and its potential for causing toxicity in humans. In addition, we also review its bio-chemical cycling in the environment; its systemic, immunotoxic, genotoxic/carcinogenic, and teratogenic health effects; and the dietary influences; as well as the important considerations in risk assessment and management of Hg poisoning have been discussed in detail. Many harmful outcomes have been reported, which will provide more awareness.